Cognitive Semantics of Social Media Themed Proverbs in Generation Z Interactions - Mega Williandani; Mulyadi Mulyadi (Randwick International of Education and Linguistics Science Journal, 2023)
Proverbs are an important aspect of language and culture that are used to describe meanings, experiences and values that are common across cultures. This article explores social media-themed proverbs that reflect Generation Z's interactions in daily life. This generation, growing up in the age of technology, views life through the lens of social media, and the proverbs expressed reflect their views on popularity, transient life, and the reality behind the online filter. By delving into proverbs such as "Not Big on Social Media, Not Small on Heart" and "Tweet a Million Words, Act a Million Meanings", this article aims to illustrate the complexity of Generation Z's interactions with social media and their awareness of responsibility and positive values in the digital world. From the analysis that has been obtained, it can be said that social media-themed proverbs are interpreted as Generation Z's behavior towards the use of social media at this time. Generation Z is virtual and superficial, relationship-related, and has short-term goals to communicate and interact in social media.